Accounting Quality and Debt Contracting - Bharath, Sreedhar T.; Sunder, Jayanthi; Sunder, Shyam V. (The Accounting Review, 2008)
We study the role of borrower accounting quality in debt contracting. Specifically, we examine how accounting quality affects the borrower's choice of private versus public debt market and how the design of debt contracts vary with accounting quality in the two markets. We find that accounting quality affects the choice of the market, with poorer accounting quality borrowers preferring private debt, i.e., bank loans. This is consistent with banks possessing superior information access and processing abilities that reduce adverse selection costs for borrowers. We also find that accounting quality has an economically significant but differential impact on contract design in the two markets consistent with differences in recontracting flexibility across the two markets. In the case of private debt, since there is greater recontracting flexibility, both the price (i.e., interest) and non-price (i.e., maturity and collateral) terms are significantly more stringent for poorer accounting quality borrowers, unlike public debt where only the price terms are more stringent. The impact of accounting quality on interest spreads of public debt is 2.5 times that of the private debt, since the price terms alone reflect the variation in accounting quality.